REVIEW OF THE PHYTOTHERAPY FOR NEPHROLITHIASIS - Ridwan, Hanna Salwa; Megantara, Sandra; Levita, Jutti (Jurnal Ilmiah Farmako Bahari, 2024)
Nephrolithiasis (kidney stone) cases have a prevalence ranging from 1% to 13%. The disease not only hampers kidney function but also elevates the risk of chronic kidney diseases. The pathophysiology of nephrolithiasis is closely linked to elevated concentrations of calcium, oxalate, and/or uric acid in the urine. Pharmacotherapy to manage nephrolithiasis includes thiazide diuretics, allopurinol, citrate supplements, and alpha-blockers that have been prescribed to relieve symptoms. In addition, there is growing interest in exploring the potential of phytotherapy. This review aims to identify suitable phytotherapy approaches by examining relevant articles on nephrolithiasis. The research methodology involved searching PubMed articles using the keywords of (("Plant Extracts") AND ("Nephrolithiasis")) OR ("Ureterolithiasis"). The articles obtained from the initial search were n =123. 2 authors screened articles for their eligibility. The inclusion criteria were limited to articles written in English, topics related to nephrolithiasis and not other kidney diseases, the botanical names of the plants and the method of extraction are clearly described, complete studies with clear descriptions regarding the methods and results, not synthetic drugs, and not involving medical instruments or laser to remove the stones. Articles included in the review were n = 17. Water and hydro-alcohol were the solvents used to extract the plants. Twenty-two plants have confirmed their anti-nephrolithiasis activity, and nine articles described the assay by in vivo study, two by in vitro study, three by both in vitro and in vivo study, and only one article mentioned a study in humans by a randomized-control trial on a mixture of herbs. It is concluded that Rhizoma alismatis, Poria cocos, Polyporus umbellatus, Atractylodis macrocephalae, and Cinnamomi Cassiae prepared as a mixture in the Wu-Ling-San formula have a potential therapeutic effect on nephrolithiasis, as this formula has been studied in humans.